2015
DOI: 10.1038/srep09930
|View full text |Cite
|
Sign up to set email alerts
|

miR-148a is Associated with Obesity and Modulates Adipocyte Differentiation of Mesenchymal Stem Cells through Wnt Signaling

Abstract: Obesity results from numerous, interacting genetic, behavioral, and physiological factors. Adipogenesis is partially regulated by several adipocyte-selective microRNAs (miRNAs) and transcription factors that regulate proliferation and differentiation of human adipose-derived mesenchymal stem cells (hMSCs-Ad). In this study, we examined the roles of adipocyte-selective miRNAs in the differentiation of hMSCs-Ad to adipocytes. Results showed that the levels of miR-148a, miR-26b, miR-30, and miR-199a increased in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
145
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(156 citation statements)
references
References 53 publications
6
145
1
4
Order By: Relevance
“…WNT signaling has also been demonstrated to be a target for miRNA mediated regulation of adipogenesis. Expression of miR-148 was elevated with obesity in mice and humans, and miR-148a was found to promote adipogenesis and impair WNT-mediated repression of adipogenesis by targeting WNT1 [24]. miR-210 has also been shown to help promote adipocyte differentiation by targeting transcription factor 7 like 2 (Tcf7l2), which acts downstream of WNT signaling [13].…”
Section: Mirnas Regulating Adipocyte Terminal Differentiation and Lipmentioning
confidence: 99%
“…WNT signaling has also been demonstrated to be a target for miRNA mediated regulation of adipogenesis. Expression of miR-148 was elevated with obesity in mice and humans, and miR-148a was found to promote adipogenesis and impair WNT-mediated repression of adipogenesis by targeting WNT1 [24]. miR-210 has also been shown to help promote adipocyte differentiation by targeting transcription factor 7 like 2 (Tcf7l2), which acts downstream of WNT signaling [13].…”
Section: Mirnas Regulating Adipocyte Terminal Differentiation and Lipmentioning
confidence: 99%
“…Additionally, miR-93 and miR-720 were lowly expressed with 5-fold in mature adipocytes compared to SVCs/hMSCs-Ad. Among these differentially expressed miRNAs, our group did further research for the adipogenic miRNAs in vivo and in vitro , including miR-148a [5], miR-26b [10], miR-146b [6] and miR-1275.…”
Section: Resultsmentioning
confidence: 99%
“…This finding has implicated miR-146b as a positive regulator of accelerated adipocyte differentiation through modulation of SIRT1 and KLF7 [6]. Indeed, our previous study found that miR-148a promotes hMSCs-Ad to differentiate to mature adipocyte by targeting Wnt1 [5]. Additionally, our group [7] has also suggested that inhibited miR-26b inhibits adipogenic differentiation in human preadipocytes, and miR-335, as a potential adipogenic miRNA, is involved in adipose tissue inflammation and is highly expressed in mature 3T3-L1 [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ectopic expression of miR-148a reportedly accelerates the differentiation of mesenchymal stem cells through Wnt signaling. 44 Further, cells expressing miR-148a have been shown to produce greater amounts of proteoglycans and collagen, in particular type II collagen, with proteoglycan and collagen secretion into culture medium shown to be inhibited, but total collagen production increased, by miR148a. 45 These corroborating studies indicate that miR-148a has multifunction roles depending on cellular conditions.…”
Section: Discussionmentioning
confidence: 99%